2016
DOI: 10.1007/s40257-016-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Bathing and Associated Treatments in Atopic Dermatitis

Abstract: Atopic dermatitis is one of the most common complaints presenting to dermatologists, and patients typically inquire as to appropriate bathing recommendations. Although many dermatologists, allergists, and primary-care practitioners provide explicit bathing instructions, recommendations regarding frequency of bathing, duration of bathing, and timing related to emollient and medication application relative to bathing vary widely. Conflicting and vague guidelines stem from knowledge related to the disparate effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 128 publications
0
25
0
5
Order By: Relevance
“…The utility of bleach baths as part of treatment of AD is contested [11]. Some studies have suggested that the effects of bleach baths reduce severity and decrease staphylococcal colonization, thereby reducing total use of topical steroids and exposure to systemic antibiotics [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The utility of bleach baths as part of treatment of AD is contested [11]. Some studies have suggested that the effects of bleach baths reduce severity and decrease staphylococcal colonization, thereby reducing total use of topical steroids and exposure to systemic antibiotics [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Wet dressings and short-term hospitalizations are other options for patients with severe, recalcitrant AD whose multiple therapies have failed. 9,53,54,[96][97][98] These treatments also are sometimes used for patients for whom treatment choices are limited due to costs and/ or insurer considerations. More information is provided in current guidance documents and several excellent reviews.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…More information is provided in current guidance documents and several excellent reviews. 9,53,54,[96][97][98]…”
Section: Other Treatmentsmentioning
confidence: 99%
“…A key feature of AD management is appropriate daily skin care. Although the frequency of bathing is somewhat controversial, most experts suggest daily bathing [ 28 ]. Bathing once or twice daily (depending on the severity of AD) in warm water for 10–15 min is recommended to help hydrate and cleanse the skin, assist in the debridement of infected skin, and improve the penetration of topical therapies.…”
Section: Treatmentmentioning
confidence: 99%